Криміналістична методика як особлива частина криміналістики - Пчеліна, Оксана Василівна; Пчелина, Оксана Васильевна; Pchelina, Oksana (Одеса : Юрид. л-ра, 2014)
The article reveals the process of establishment and development of criminalistical methods of investigation as a section of criminalistics. The content of criminalistical methods of investigation and its place in criminalistics science are determined.
Пчеліна О. В. Криміналістична методика як особлива частина криміналістики / О. В. Пчеліна // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 396-401.
Keywords: криміналістична методика; розділ; особлива частина; криміналістика; криминалистическая методика; раздел; особенная часть; криминалистика; criminalistical methods of investigation; section; special part; criminalistics